Piaget. - "Boden, Margaret A." (Glasgow, 1979)
This book is for anyone who has ever wondered how a child develops language, thought, and knowledge. Before this classic appeared, little was known of the way children think.The book has since been a source of inspiration and guidance to generations of parents and teachers. While its conclusions remain contentious to this very day, few can deny the huge debt we owe to this pioneering work in our continuing attempts to understand the minds of the child.
Keywords: "Piaget, Jean, 1896-1980 Biography"